The kitten who cried dog - Guillain, Charlotte; Aesop; Beacon, Dawn (Chicago, Ill Raintree, 2013)
A simplified version of the familiar fable featuring a kitten who becomes bored with guarding a stack of toys and decides to cry "dog" and watch the villagers come running, until the day a dog is really there and no one answers his call. Includes a note on the history of the tale
A gift from book Africa
English storeies
1 2 13
Keywords: Aesop's fables; Boy who cried wolf -- Adaptations -- Juvenile literature